2019
DOI: 10.1177/1354067x19839070
|View full text |Cite
|
Sign up to set email alerts
|

Re-theorising the funds of identity concept from the perspective of subjectivity

Abstract: This paper is a theoretical response to recent developments in the funds of identity literature which has seen the introduction of two interconnected concepts, ‘dark funds of identity’ and ‘existential funds of identity’. While these recent concepts may expand the canvas from which researchers draw in developing interventionist approaches for minoritised students, they nevertheless polarise positive and negative emotions and experiences which is problematic on a conceptual level. This paper addresses this issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Finally, most studies reported on participants describing positive aspects of their lives, such as people whom they value. However, proposals are made to also focus on FoI that are linked to negative experiences (Poole, 2020; Poole & Huang, 2018). These types of FoI create challenges for teachers, who may feel that they lack the resources or training to support students in life struggles that are revealed, echoing a difficulty experienced by Australian teachers when they learnt about students’ dark FoK (Zipin, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, most studies reported on participants describing positive aspects of their lives, such as people whom they value. However, proposals are made to also focus on FoI that are linked to negative experiences (Poole, 2020; Poole & Huang, 2018). These types of FoI create challenges for teachers, who may feel that they lack the resources or training to support students in life struggles that are revealed, echoing a difficulty experienced by Australian teachers when they learnt about students’ dark FoK (Zipin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, FoI are not completely internal but are embedded in the social fabric of life. Some researchers have noted (Hviid & Villadsen, 2014; Poole, 2020) that Esteban-Guitart’s (2014) distinction between five categories of FoI (geographical, practical, cultural, social, and institutional) may reify FoI and imply “a symbolic essence of things which the individual, through his/hers (sic) development, will come to discover” (Hviid & Villadsen, 2014, p. 64). We understand this categorization as a proposal of sensitizing concepts, offering a language that may help discuss possible FoI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations